Empreendimentos turísticos e impactos ambientais no Distrito de Jacumã, Município do Conde - PB - Guedes, Joelma Abrantes (2005)
The study area is the district of Jacumã, city of Conde, which is located on the south coast of the Paraíba state. A landscape of beaches, cliffs, estuaries, coral reef and other important physical features make up the high tourist potential of that tract of the Paraíba state. The natural attractiveness of the area has led the public sector to encourage the development of the region based on tourism. After the inauguration of the PB-008 highway in 2000 significant urban expansion has taken place with the development of a large number of tourist enterprises. However, the unplanned occupation of the area without any consideration of the relevant legislation has caused severe environmental impacts. This unplanned tourist development has worsen the local infrastructure deficiencies and eroded the outstanding natural landscape and ecosystems that function as the main draw on the tourist demand. Jacumã s tourist enterprises were inventoried and the inns and restaurants that have caused environmental negative impacts were identified on the basis on their capacity to generate solid waste, being located on protected areas or on areas that have legal restrictions to occupation. The level of the impacts was mapped and evaluated. The inventory was carried out using questionnaires and interviews with owners on tourist enterprises. In addition, overlay mapping of the area was implemented with the use of a Geographic Information System in conjunction the McHarg methodology and Priorization with Pareto. Results demonstrated that nine out of the 30 inns included in the study are located in areas with legal restrictions and four other inns are located in areas with high legal restrictions. Also, 10 out of the 12 restaurants included in the study are located in areas with legal restrictions. These findings give evidence of the need for planning and environmental zoning of the area in order for the relevant environmental legislation to be respected. The environmental legislation aims at protecting the important ecosystems of the study area in such a way that if tourism impacts on the local environment and reduce the area s tourist potential, the quality of life of the local population is not degraded